PENGARUH RISIKO LIKUIDITAS DAN RISIKO OPERASIONAL TERHADAP PROFITABILITAS PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK PERIODE 2017-2022 - Anis Feblin; Rr. Dimas Veronica Priharti; Mir’atul Hasanah (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
The purpose of this research was to determine the influence of liquidity risk and operational risk on profitability at PT. Bank Negara Indonesia (Persero) Tbk 2017-2022 Period. The analytical method used in this research was multiple linear regression with a significance level of 5%. Apart from that, this research also carried out classical assumption tests which includes normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The type of data used in this research was secondary data obtained from the company's official website (www.bni.co.id). From the results of tests carried out in this research, it was known that partially Liquidity Risk (LDR) and Operational Risk (BOPO) influenced Profitability (ROA) at PT. Bank Negara Indonesia (Persero) Tbk for the 2017-2022 period had a significant influence, while the results of simultaneous testing of Liquidity Risk (LDR) had no significant influence on Profitability (ROA) and Operational Risk (BOPO) had a significant influence on Profitability (ROA). The results of the R Square coefficient of determination analysis were 0.927 or 92.7%, this showed that the percentage contribution of the influence of Liquidity Risk (X1) and Operational Risk (X2) on the rise and fall of Profitability (Y) was 92.7% while the remaining 2.3% was influenced by other variables not examined in this study.